Diskursus Sekolah Rakyat dalam Agenda SDGs 4: Respons Kebijakan terhadap Ketimpangan Akses Pendidikan di Kota Pasuruan - Nayshira Rieva Candra; Alifatu Azwa Shoima; Firre An Supraptop; Indah Prabawati (CV. Ulil Albab Corp, 2026)
This study analyses the discourse surrounding the People’s School as an innovative policy response to inequalities in access to education education within the framework of Sustainable Development Goals (SDGs) 4 in Pasuruan City, East Java. Adopting a qualitative approaach through literature review and policy document analysis, this study reveals the dynamics of structural exlusion underpinning disparities in access to education. The finding indicate that the School Participation Rate (TPS) is quite high at primary and lower secondary levels, there is a significant decline at upper secondary level. This reflects the economic, geographical and social barries faced by vulnerable groups, such as children who do not continue their education from poor families living in urban areas and girls in sub urban areas. People’s Schools have emerged as an alternative inclusive policy that not only expands access to free and flexible education, but also funcions as an affirmative instrument through socio economic support programmes, such as living cost assistance, career conselling, and avocational curriculum integrity. These findings suggest the potential for people’s to accerelate the realisation SDGs 4, whils suggesting improvements to national regulations so that similar models can be replicated in other regions to sustainably reduce structural inequalities.